2012
DOI: 10.1055/s-0032-1305785
|View full text |Cite
|
Sign up to set email alerts
|

Lower Branches of the Facial Nerve

Abstract: Various aesthetic procedures have been developed over the past several decades for facial rejuvenation. One of the parallel goals is protection of vital structures such as the facial nerve. In this study, 10 cadaveric hemifacial dissections were performed, and the course of the lower portion of the facial nerve was studied with specific attention addressed toward the three-dimensional location of the nerve as it relates to the usual superficial tissue planes that are dissected during the course of an open faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…32 In their landmark study, Dingman and Grabb studied 100 facial halves and found two or greater rami in nearly 80 percent of their dissections. 12 They also found that the marginal mandibular nerve anterior to the facial vessels was above the lower border of the mandible in 100 percent of their dissections.…”
Section: Marginal Mandibular Branchmentioning
confidence: 99%
“…32 In their landmark study, Dingman and Grabb studied 100 facial halves and found two or greater rami in nearly 80 percent of their dissections. 12 They also found that the marginal mandibular nerve anterior to the facial vessels was above the lower border of the mandible in 100 percent of their dissections.…”
Section: Marginal Mandibular Branchmentioning
confidence: 99%